Nanostructured Silica–Titania Hybrid using Dendritic Fibrous Nanosilica as a Photocatalyst. Issue 10 (24th April 2017) - Bayal, Nisha; Singh, Rustam; Polshettiwar, Vivek
Abstract: A new method has been developed to fabricate active TiO2 photocatalysts by tuning the morphology of the catalyst support. A sustainable solution‐phase TiO2 deposition on dendritic fibrous nanosilica (DFNS) protocol is developed, which is better than the complex and expensive atomic layer deposition technique. In general, catalytic activity decreases with an increased TiO2 loading on conventional mesoporous silica because of the loss of the surface area caused by the blocking of pores. Notably, in the case of the dendritic fibrous nanosilica KCC‐1 as a support, because of its open fibrous morphology, even at the highest TiO2 loading, a relatively large amount of surface area remained intact. This improved the accessibility of active sites, which increased the catalytic performance of the KCC‐1/TiO2 photocatalyst. KCC‐1‐supported TiO2 is a superior photocatalyst in terms of H2 generation (26.4 mmol g TiO 2 −1 h −1 ) under UV light. This study may provide a new direction for photocatalyst development through the morphology control of the support. Abstract : Fibrous photocatalyst : A new method is developed to fabricate active TiO2 photocatalysts by tuning the morphology of the catalyst support through solution‐phase TiO2 deposition on silica. With the nanosilica KCC‐1 as a support, a relatively large amount of surface area remains intact because of its open fibrous morphology, even at the highest TiO2 loading. This improves the accessibility of active sites, which increases the catalytic performance of the KCC‐1/TiO2 photocatalyst.